Differences in Thickness Variation of Absorbing Media from Patchwork and Plywood Waste on Noise Intensity Reduction - Zulpha, Lulu; Djuhriah, Nany; Fikri, Elanda (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Noise is one of the most dangerous factors in the work environment, so it is essential to control it. This study aims to determine the variation in the thickness of the damping medium from patchwork and plywood waste, with a focus on reducing the intensity of noise in yarn cutting machines. This study iThis study employs an experimental pretest-posttest design without a control group. population comprises all noise sources present in the production room of PT Trisula Textille Industries. The yarn-cutting machine with the highest noise is the sample used in this study. The sampling technique is purposive sampling. The test was carried out on 36 noise, temperature, and humidity measurement results. The results of noise intensity measurements before treatment ranged from 97.26–97.43 dBA. After applying variance 1 dampers, the average noise intensity decreased by 5.66%, variation 2 by 8.89%, and variation 3 by 11.89%. The one-way ANOVA test shows a p value of 0.0001 or < 0.05. According to the decision rules, it means that there is a difference in each thickness variation has a difference. When applied in areas with high noise levels, industries can use thicker plywood boards and install wheels on the dampers so that the tools can be used practically. Researchers can then use different types of damping media and thicker patchwork variations.